Medial Position and Counterclockwise Rotation of the Parietal Scalp Hair-Whorl as a Possible Indicator for Non-Right-Handedness. (2008) - Schmidt, Heinrich; Depner, Martin; Kabesch, Michael
Abstract : The objective of our study was to assess the association between position and swirling direction of the parietal whorl (PW) and handedness. In 519 patients of a pediatric practice, PWs were located and the swirling direction determined. Of those patients, handedness could be specified in 217. The right-sided PW (n = 347; 70.8%) and the clockwise (CW) swirling type (n = 411; 83.9%) of all participants were predominant in children with one PW. Non-right-handedness (NRH) was found in 40 (18.4%). Medial position of the whorl per se increases the chance for NRH, indifferent of the swirling direction. In patients with counterclockwise (CCW) swirling, the chance of NRH increased 3.5-fold for the right-sided, 5.4-fold for the left-sided, and 12.9-fold for the medial-positioned whorl. We conclude that NRH is associated with the position (medial!) and the swirling direction (CCW!) of the PW.